Rethinking Forestry and Natural Resources Higher Education in Ethiopia: An Education for Sustainable Development Perspective - Gessesse Dessie; Menfese Tadesse (Environmental Association of Southern Africa, 2013)
This article reports on an action research project to reorient forestry and natural resources higher education in Ethiopia. The study used a combination of methods, including questionnaires and secondary information, to understand the existing higher-education system in Ethiopia. Based on the initial analysis, a workshop was held to deliberate the findings and to draw up guidelines for forestry and natural resources higher education that reflect education for sustainable development (ESD) approaches. The results of the study show that the state of higher education with regard to forestry and natural resources has, in about half a century of such education, been influenced by several internal and external factors. It progressively evolved from endeavours dependent on foreign aid to a self-sufficient Ethiopian system. During this time, the structural distribution of graduates moved in emphasis from an earlier emphasis on the diploma to a BSc-level emphasis. Little progress has been made with regard to female graduates, student enrolment is limited and the desirability of forestry education has declined. Despite this, most of the 31 public universities in the country offer natural resources education. Curricula were found to be inadequate for the challenges of the times, as was the national demand for expert professionals. Existing epistemological foundation adheres to forestry as a commodity rather than as a social-ecological system influencing conceptual definitions of forest, forestry and forester. Within an ESD perspective, forests are identified as social-ecological systems, forestry is seen as a sustainability science and a sustainable development sector, and the forester is viewed as a systems thinker and change agent. It is agreed that higher education relating to forestry and natural resources in Ethiopia requires guidelines that encompass a non-reductionist and comprehensive disciplinary base where synergy of multidisciplinary approaches is emphasised, as in ESD. The guidelines outlined indicate how to adapt higher education in respect of forestry and natural resources to changing societal needs in Ethiopia. The emerging guidelines also point to a reorientation of academic institutional foundations and leadership and to the need for a relevant epistemological framework to guide higher-education curricula on forestry and natural resources. The emerging guidelines further stress that higher education should engage more strongly with pertinent global and national issues.